E-076 Fistulae at the Falx and Tentorium cerebelli; Liverpool series. (14th July 2013) - Nahser, H; Puthuran, M; Chandran, A; Javadpour, M; Eldridge, P
Abstract : Dural arteriovenous fistulae at the falx and at the an terior and posterior margin of the tentorium cerebelli drain into cortical veins exclusively and their most common mode of presentation is haemorrhage. The concept of dural fistulae that involve smaller sinuses at the tent and falx was introduced by PICARD (1990, Journal of Neuroradiologie 17, 161–181). We have retrospectively analysed a series of patients treated in between 2002 and 2012. 12 were found to be located at the falx and 30 located at the tent. One patient with an unruptured fistula died before treatment because of a haemorrhage. All other patients except one were treated initially with embolisation via feeding meningeal arteries with Onyx. This lead to radioanatomic cure in all but sixth patients. In the completely obliterated we observed that during this single feeder injection of Onyx 20 or 34 led to penetration to the origin of the first draining vein at the tentorial or falcine sinus and could then, with continued injection, retrogradely penetrate into the distal parts of the other feeding arteries leading to complete arterial disconnection from the venous side. In two patients for safety reasons to block retrograde embolisation of the internal carotid artery via the artery of Bernasconi, the internal carotid artery was temporarily blocked with a balloon at the origin of this branch during injection. One patient primarily and 3 others were then successfully occluded by surgery, the remaining by an endovascular transvenous approach with injection of Onyx. No lethal or complications with persistent disabling morbidity were recorded. Disclosures: H. Nahser: 6; C; Support for Travel to meetings by various companies. M. Puthuran: 6; C; Support for Travel by various companies. A. Chandran: None. M. Javadpour: 6; C; Support for Travel to meetings by various companies. P. Eldridge: 6; C; support for Travel to meetings by various companies.